Tahapan dan Strategi Pembelajaran Baca Al Qur’an Tunarungu dengan Taraf Sangat Berat - Cahya Ningrum, Figitha; Dzulfikar Akbar Romadlon (PAI RAFAH, 2024)
Islamic religion in particular is an important component of education that must be taught to all students, even those who are deaf. Due to their hearing limitations, deaf children have special difficulties when learning the Qur'ān. Qur'ānic learning strategies for severely deaf children - that is, children who have both deafness and hearing loss - will be discussed in this article. Children who are severely deaf and have low literacy levels will have difficulty understanding the language around them. The technique of lip reading and writing Hijaiyah letters is used in the Qur'ānic learning method used in this study. Deaf children are instructed to practice their lips according to the makhorijul of the hijaiyah letters. It takes about six months to learn the hijaiyah letters by heart, with specific learning stages and techniques used. A descriptive qualitative methodology combining observation, interviews and documentation was used in this study. The information collected is presented in the form of images, videos and text. This research provides an alternative to efficiently teach deaf children to recite the Qur'an through the application of this method. The illiteracy difficulties in Indonesian society are also reflected in the importance of Qur'ānic education for deaf children. Thus, this new approach is expected to